On the three-dimensional vortical structure of early diastolic flow in a patient-specific left ventricle - Le, Trung Bao (2012)
We study the formation of the mitral vortex ring during early diastolic filling in a patient-specific left ventricle using direct numerical simulation. The geometry of the left ventricle is reconstructed from Magnetic Resonance Imaging (MRI). The heart wall motion is modeled by a cell-based activation methodology, which yields physiologic kinematics with heart rate equal to 52 beats per minute. We show that the structure of the mitral vortex ring consists of the main vortex ring and trailing vortex tubes, which originate at the heart wall. The trailing vortex tubes play an important role in exciting twisting circumferential instability modes of the mitral vortex ring. At the end of diastole, the vortex ring impinges on the wall and the intraventricular flow transitions to a weak turbulent state. Our results can be used to help interprete and analyze three-dimensional in–vivo flow measurements obtained with MRI.